Lipid Peroxidation Product and Glutathione Levels in Patients with Coronary Heart Disease Before and After Surgery - Khansha, Rahman; Miladpour, Behnoosh; Mostafavi-Pour, Zohreh; Zal, Fatemeh (Galen Medical Journal, 2015)
Background: It has been reported that ischemia-reperfusion is associated with augmentation of oxidative stress and its specific and sensitive markers. Oxidative stress may cause atrial fibrillation (AF) which is a common consequence after cardiac surgery. Dietary supplementation with antioxidants might lower the incidence of AF following coronary artery bypass graft (CABG) surgery. Materials and Methods: Fifty patients with coronary heart disease (CHD) referred to Namazi and Faghihi Hospitals in Shiraz, undergone elective CABG, were enrolled in this study. For evaluation of oxidative stress, whole blood was taken before and 24 hours after surgery and malondialdehyde (MDA) as an oxidative marker and glutathione (GSH) as an antioxidant marker were measured. Results: Results showed a significant difference between the mean concentration of GSH before and after CABG surgery (P <0.05); however, the difference in plasma MDA levels before and after CABG was insignificant. Conclusion: CABG surgery results in oxidative stress and reduces GSH 24h after surgery and administration of antioxidants may attenuate post-operative oxidative stress. [GMJ.2015;4(2):78-82]